2013
DOI: 10.4314/gjass.v12i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Technology and market opportunities in fiber cement composites for small scale enterprises in Nigeria

Abstract: Solving problems of unemployment and developing new materials for buildings requires moving beyond the traditional approaches to more economical, environmentally benign performance models and design properties. New approaches should develop models based on the literature and a full understanding of the root causes of failure, derived from careful failure analysis. One of the main drivers of the development efforts in fibre based composites is the trend towards greater environmental awareness and the health haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Waste fibres have been used to reinforce plastics, cement and other hydrophobic polymers, and there has been an increased effort towards promoting a circular bioeconomy by recycling these materials in new composite products [8,9]. The use of waste fibre-reinforced composites in housing construction will not only alleviate the pressures of overexploitation of plant-based fibres, but also serve as avenues 1 3 for the utilization of abundant waste fibres generated in paper recycling mills [10].…”
Section: Introductionmentioning
confidence: 99%
“…Waste fibres have been used to reinforce plastics, cement and other hydrophobic polymers, and there has been an increased effort towards promoting a circular bioeconomy by recycling these materials in new composite products [8,9]. The use of waste fibre-reinforced composites in housing construction will not only alleviate the pressures of overexploitation of plant-based fibres, but also serve as avenues 1 3 for the utilization of abundant waste fibres generated in paper recycling mills [10].…”
Section: Introductionmentioning
confidence: 99%
“…The fibres content depends on their tendency to aggregate [12] and it is crucial that the fibres are being properly mixed and evenly dispersed throughout the matrix [7,13]. Although tests have shown that such natural fibre-based mortars are characterized by satisfying tensile and flexural strength, fine powdered fibres do not significantly contribute to bridging qualities following micro-crack development and instead, primarily serve as fillers [14]. Additionally, for a range of fibre contents, flexural strength, fracture toughness and dimensional stability all increase as the fibres length rises and as their diameter declines [15,16].…”
Section: Introductionmentioning
confidence: 99%